Chimpanzees (Pan troglodytes) Tolerate Some Degree Of Inequity While Cooperating But Refuse To Donate Effort For Nothing - Campbell, Matthew W. (Am J Primatol, 2020)
In cooperative hunting, a carcass cannot be divided equally, and hunts may be unsuccessful. We studied how chimpanzees respond to these two variables, working for unequal rewards and no rewards, which have been rarely included in experimental cooperative tasks. We presented chimpanzees with a task requiring three chimpanzees to work together and varied the reward structure in two separate experiments. In experiment 1, two individuals received more rewards than the third, making the outcome unequal. We wanted to know if cooperation would continue or break down, and what mechanisms might maintain performance. Experiment 2 used equal rewards, but this time one or more locations were left unbaited on a proportion of trials. Thus, there was the chance of individuals working to receive nothing. In experiment 1, the chimpanzees worked at a high rate, tolerating the unequal outcomes, with rank appearing to determine who got access to the higher value locations. However, equal outcomes (used as a control) enhanced cooperative performance, most likely through motivational processes rather than the absence of inequity aversion. In experiment 2, performance dropped off dramatically when the chimpanzees were not rewarded on every trial. Their strategy was irrational as donating effort would have led to more rewards in the long run for each individual. Our results lead to a hierarchy of performances by condition with equity > inequity > donating effort. Chimpanzees therefore tolerate mild inequity, but cannot tolerate receiving nothing when others are rewarded.